Migrants latino-américains à Madrid : quelles stratégies pour la reconnaissance professionnelle ? - Sylvie Koller (Les Cahiers ALHIM)
The Latin-American migratory flow  is part and parcel of the immigration boom of immigration that Spain underwent during the last decade of the 20th century with a higher proportion in Madrid compared to other regions. Some of these migrants are university graduates in their home country with work experience. Yet most of them occupy unskilled or low-skill jobs, with some differences depending on country of origin. This down-grading, which goes largely unrecognised, is totally ignored by government policies. However, those concerned by the difficulties in getting recognition of their qualifications have adopted a variety of individual strategies to avoid unskilled jobs. Group structures have also appeared to help increase awareness of the existence of these skilled workers and to strengthen their case. What kind of regroupings ? What are the chances of success ?